Effect of propolis on Th2 and Th17 cells: interplay with EtxB-and LPS-treated dendritic cells - Conti, B. J. [UNESP]; Santiago, K. B. [UNESP]; Cardoso, E. O. [UNESP]; Conte, F. L. [UNESP]; Golim, M. A. [UNESP]; Cruz, M. T.; Sforcin, J. M. [UNESP] (FapUNIFESP (SciELO), 2023)
Dendritic cells (DCs) are antigen-presenting cells that drive the differentiation of T CD4+ cells into different profiles according to the nature of the antigen or immunomodulator. Propolis is a resinous product made by bees that has numerous pharmacological properties, including an immunomodulatory action. To assess whether propolis can modulate the activation of CD4+ T cells by stimulating DCs with heat-labile enterotoxin B subunit (EtxB) or lipopolysaccharide (LPS), we aimed to elucidate the mechanisms affected by propolis in the differential activation of T lymphocytes. Cell viability, lymphocyte proliferation, gene expression (GATA-3 and RORc), and cytokine production (interleukin (IL)-4 and IL-17A) were analyzed. Propolis, EtxB, and LPS induced a higher lymphoproliferation compared with the control. Propolis induced GATA-3 expression and, in combination with EtxB, maintained the baseline levels. Propolis alone or in combination with LPS inhibited RORc expression. EtxB alone and in combination with propolis increased IL-4 production. Propolis in combination with LPS prevented LPS-induced IL-17A production. These results opened perspectives for the study of biological events that may be favored by propolis by promoting Th2 activation or helping in the treatment of inflammatory conditions mediated by Th17 cells.
Keywords: CD4+ T cells; Dendritic cells; Immunomodulation; Propolis